Circular - Schevenels, Walther, b. 1894
029-0003-001 FÉDÉRATION SYNDICALE INTERNATIONALE INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONALER GEWERKSCHAFTSBUND 9, AVENUE D'ORSAY, PARIS-VIIe ADRESSE TÉLÉGRAPHIQUE: TELEGRAPHIC ADDRESS: } INTERFED. PARIS TÉLÉPHONE : INVALIDES 45-88 TELEGRAMM ADRESSE: F.I. de Sol. 407 Sch/H/G. 7th April, 1937, To Affiliated National Centres. Dear Comrades, We have just received from our comrades of the Unión General de Trabajadores (Spanish National Trade Union Centre) a letter of which the translation follows: "We learn daily through the press of the arrival in Spain of medical supplies, food supplies and clothing sent for the combattants by the sections of your International; these consignments are accompanied by delegations of the respective organisations. On their arrival at Valencia, these delegations are met by elements belonging to political organisations which have no connection with the UGT, which sometimes take action with the International Red Aid and proceed to distribute the gifts which have been brought without the UGT knowing anything at all about who has sent the consignment, where it is delivered or who is in charge of the goods sent to Spain. As this represents an anomaly which makes very difficult the work of solidarity for our cause which the circumstances demand, we regard it as indispensable for you to ask all the sections of the International to inform the UGT of all that they are sending to Spain, so that we can state in the press that the consignments are coming from the IFTU, and can make known, in the way required by the circumstances, the solidarity which is being evinced." We have informed our Spanish comrades that we will at once make known their wishes to our National Centres. We have however pointed out in our reply that the IFTU - as also the LSI - has right from the outset emphasised in all its appeals for aid that all relief work, all contributions and all consignments should be centralised and co-ordinated within the International Solidarity Fund. The International Solidarity Fund got into touch right at the beginning with the Spanish organisations (UGT and Spanish Socialist Party) and set up a Relief Committee in Spain itself with a view to this co-ordination. This Committee is composed of Carlos Hernandez, representing the UGT, and Enrique Santiago, representing the Spanish Socialist Party and all the relief work carried on by the International Solidarity Fund has been effected through this Spanish Committee or through its representatives in Bilbao, Gijon, Santander, Alicante, Valencia and Barcelona, which provides the best guarantee for the coordination of all relief work. We would therefore emphasise once again, in view of the wishes expressed by our Spanish Comrades, that all relief work carried on by our National Centres, under their auspices or with their collaboration should go through the International Solidarity Fund, of which the seat is in Paris, or at least that the ISF should be informed of consignments sent to Spain. Yours sincerely, W. Schevenels, General Secretary. 292/946/29/3